Long-lasting electromagnetic ion cyclotron wave signatures at Indian Antarctic Station, Maitri - Kakad, Amar; Upadhyay, Aditi; Kakad, Bharati; Rawat, Rahul (My University, 2022)
The long-lasting, persistence electromagnetic ion cyclotron (EMIC) waves can have a profound effect on the dynamics of the relativistic electrons in the Earth’s radiation belt. EMIC waves observed on the ground are the manifestation of their generation in the Earth’s inner magnetosphere. With the spacecraft measurements, it is difficult to determine their spatio-temporal extent and sustainability. In this context, in addition to the spacecraft observations the ground observations can give better insights into these features. We have identified the long-duration EMIC wave events observed at the subauroal station Maitri during 2011–2017. We have found a total of 12 EMIC wave events that are steadily observed for >10 h. The start times of these events are identified between 1.4–9.3 LT hours, and they lasted for 10–18 h. All these events are dominantly seen during the recovery phase of the weak-moderate geomagnetic storm. Comparison with spacecraft observations indicate the simultaneous EMIC waves in the magnetosphere within L–shell 4–6 with wider longitudinal coverage, and sufficiently long time presence in the magnetosphere. Simultaneous differential electron flux observations from Van Allen Probes indicate that approximately 90% of these EMIC waves were accompanied by a decrease in relativistic (2.6–4.2 MeV) electrons in the outer radiation belts.
Keywords: EMIC wave occurrence; Inner magnetosphere; Pc1-Pc2 pulsations; Long-duration events; Radiation belts